The Ways of Formation of Future Translators’ Readiness to Perform Professional Activities in the Conditions of War - Ivashkevych, Ernest (Problemi sučasnoï psihologìï (Online), 2022)
the purpose of our research is to characterize the ways of assessing the readiness of future translators to perform professional activities in the condi-tions of war; to identify the level of formation of students’ motivational, seman-tic, operational and value readiness to perform translation activities.methods of the research. The following theoretical methods of the research were used to solve the tasks formulated in the article: a categorical method, structural and functional methods, the methods of the analysis, systematization, modeling, generalization. The empirical method is ascertaining research. he results of the research. So, the professional development of the indivi-dual can take place in several stages. The first stage is considered to be pre-pro-fessional training, the main purpose of which is the professional self-determina-tion of the individual, the formation of the attitude towards a certain profession, and the realization of the person’s conscious choice of his/her professional acti-vity. This is the process of forming the individual’s attitude towards himself/her-self as a subject of future professional activity, which in a long period of time will help a person adapt to life as a whole. Pre-professional training is interpreted as the preparation of the polytechnic and professional character of students, as a basic component of their further professional training.conclusions. Thus, professional formation is a process, which has the aim of the development and the formation of the personality of a future specialist as a subject of professional education and activity. We proved, that the subjec-tive qualities of a specialist are mainly determined by his/her subjective posi-tion, which should be defined as a kind of integration of the dominant sovereign qualities of a professional, which are decisive in any significant professional is-sues or problems for a specialist. The subjective position of a specialist is a ba-sic, a dominant component in the professional model of personality’s formation, a fundamental characteristic of his/her behavior in the profession. Subjectivity presupposes, first of all, the formation of worldview guidelines, moral and va-luable qualities of the individual, which determine not only the active position of the professional, but also the worldview orientations of the specialist.